An updated look at the recovery of agricultural productivity in Sub-Saharan Africa - Nin-Pratt, Alejandro; Yu, Bingxin (International Food Policy Research Institute, 2008)
We analyze the evolution of Sub-Saharan Africa's agricultural total factor productivity (TFP) over the past 40 years, looking for evidence of recent changes in growth patterns using a nonparametric Malmquist index. Our TFP estimates show a remarkable recovery in the performance of Sub-Saharan Africa's agriculture during the 1984-2003 period after a long period of poor performance and decline. That recovery is the consequence of improved efficiency in production resulting from changes in the output structure and an adjustment in the use of inputs, including an overall net reduction in fertilizer use but increased fertilizer use in most of the best-performing countries. Policy changes African countries conducted between the mid-1980s and the second half of the 1990s together with technological innovations available at that time appear to have played an important role in improving agriculture's performance. As TFP growth in Sub-Saharan Africa is mainly a result of catching up to the frontier, we expect growth to slow in the coming years unless African countries accelerate the incorporation of innovations into the production process and increase the speed of technical change.--Authors' Abstract